Machine translation systems and guidebooks: an approach to the importance of the role of the human translator - Fuentes-Luque, Adrián; Santamaría Urbieta, Alexandra (Onomazein, 2021)
Computer-assisted translation tools are increasingly supplemented by the presence of machine translation (MT) in different areas and working environments, from technical translation to translation in international organizations. MT is also present in the translation of tourism texts, from brochures to food menus, websites and tourist guides. Its need or suitability for use is the subject of growing debate. This article presents a comparative analysis of tourist guides translated by a human translator and three machine translation systems. The aims are to determine a first approach to the level of quality of machine translation in tourist texts and to establish whether some tourist texts can be translated using machine translation alone or whether human participation is necessary, either for the complete translation of the text or only for post-editing tasks.
Keywords: machine translation; tourist translation; post-editing; human translator; translation quality; JCR; Scopus